2021
DOI: 10.1200/jco.20.02438
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Radiotherapy With Adjuvant Androgen Deprivation Therapy (ADT) Improves Metastasis-Free Survival Compared to Neoadjuvant ADT: An Individual Patient Meta-Analysis

Abstract: PURPOSE There remains a lack of clarity regarding the influence of sequencing of androgen deprivation therapy (ADT) and radiotherapy (RT) on outcomes in prostate cancer (PCa). Herein, we evaluate the optimal sequencing of ADT with prostate-directed RT in localized PCa. METHODS MEDLINE (1966-2018), Embase (1982-2018), ClinicalTrials.gov, and conference proceedings (1990-2018) were searched to identify randomized trials evaluating the sequencing, but not duration, of ADT with RT. Two randomized phase III trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 34 publications
5
38
1
Order By: Relevance
“…3 Although we fully agree with the dangers of multiple testing and unplanned subgroup analyses, much of what they have stated are in fact strengths of randomization and limitations of observational research, especially in the context of our paper. 3 Every study design, including meta-analyses, has strengths and limitations. The strength of a metaanalysis is to capture the heterogeneity of study designs, broad inclusion criteria, treatment differences, and other potential biases or confounders, and finally to determine if a consistent treatment effect can be observed by virtue of a large sample size and consequently a greater power to detect differences that might be missed by individual trials.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…3 Although we fully agree with the dangers of multiple testing and unplanned subgroup analyses, much of what they have stated are in fact strengths of randomization and limitations of observational research, especially in the context of our paper. 3 Every study design, including meta-analyses, has strengths and limitations. The strength of a metaanalysis is to capture the heterogeneity of study designs, broad inclusion criteria, treatment differences, and other potential biases or confounders, and finally to determine if a consistent treatment effect can be observed by virtue of a large sample size and consequently a greater power to detect differences that might be missed by individual trials.…”
supporting
confidence: 59%
“…An important consideration of any meta-analysis is the credibility of the results. 3 First, we used the randomized designs from both trials, which is critical to minimize unaccounted forms of bias between study arms. In fact, we used the entire Ottawa 0101 trial and the entire prostate-only randomized cohort in RTOG 9413.…”
mentioning
confidence: 99%
“…Findings from both these studies raised a possibility of superior biochemical relapse-free survival or progression-free survival with adjuvant ADT with prostate directed radiotherapy, respectively [29,36]. An individual patient databased meta-analysis of these two studies demonstrated that the sequencing of ADT with prostate-directed RT has significant impact on long-term oncologic outcomes in patients with localized prostate cancer [37]. Up to a 15-year truncation point in follow-up, restricted mean survival time for progression was significantly higher with adjuvant ADT with an absolute difference of 10.8 months (95% CI: 2.7-18.8), favoring the adjuvant approach.…”
Section: Systemic Therapy For High-risk Prostate Cancermentioning
confidence: 99%
“…Given that this analysis excluded patients receiving pelvic nodal irradiation, the discrepancy with our findings may be related ot the impact of treatment volumes on the optimal timing of ADT initiation as, suggested by RTOG 9413 (9). Further, ADT duration among all patients in this meta-analysis was six months, making these data less generalizable to a modern HR-PC cohort (18). patients treated with <60 Gy to prevent the inclusion of patients who treated with palliative intent.…”
Section: Discussionmentioning
confidence: 56%
“…In the RTOG 9413 trial, neoadjuvant ADT initiation benefited patients treated with whole-pelvic RT but not prostate-only RT (9). A recent meta-analysis of the patients treated with prostate-only RT from the RTOG 9413 and Ottawa 0101 trials found improved metastasis-free survival with concurrent ADT initiation as compared to neoadjuvant ADT initiation (18). Given that this analysis excluded patients receiving pelvic nodal irradiation, the discrepancy with our findings may be related ot the impact of treatment volumes on the optimal timing of ADT initiation as, suggested by RTOG 9413 (9).…”
Section: Discussionmentioning
confidence: 99%